Comparison of the Short-Term Effectiveness of Short-Wave Diathermy Treatment in Patients With Carpal Tunnel Syndrome: A Randomized Controlled Trial - Ahmet BOYACI; Ahmet TUTOĞLU; İrfan KOCA and Özcan KOCATÜRK and Esra ÇELEN (Archives of Rheumatology, 2014)
Objectives: This study aims to compare the effects of pulsed and continuous short wave diathermy (SWD) treatment in carpal tunnel syndrome. Patients and methods: This double-blind, randomized controlled trial included 30 patients (55 wrists) diagnosed with mild or moderate carpal tunnel syndrome. Patients were randomized into three groups and administered splinting and one of the following treatments: group 1: continuous SWD, group 2: pulsed SWD, and group 3: placebo SWD. The treatment was applied five days a week for 15 sessions. Patients were evaluated by the Tinel’s test, Phalen’s and reverse Phalen’s maneuvers, carpal compression test, the Boston Carpal Tunnel Questionnaire (BCTQ: includes 2 parts, namely the symptom severity scale and functional status scale), and a visual analog scale. Median motor distal latency, median sensory distal latency, and nerve conduction velocity were measured. Electrophysiological findings, clinical tests, and scales were evaluated at the beginning and end of the therapy. Results: A significant difference was observed in Phalen’s maneuver positivity in the pulsed SWD group (p<0.05). Visual analog scale, BCTQfunctional status scale, BCTQ-symptom severity scale, median nerve motor and sensory latencies, and sensory nerve conduction velocity values were improved in both continuous and pulsed SWD groups (p<0.05). The placebo group also showed improved BCTQ-functional status scale and median nerve motor distal latency (p<0.05). Boston Carpal Tunnel Questionnaire-symptom severity scale improved more in the continuous SWD group than the other groups (p<0.01), and improved median nerve sensory distal latency and nerve conduction velocity parameters were observed in both SWD groups than the control group (p<0.01). Conclusion: Continuous and pulsed SWD therapies supported with splinting were effective for improving pain, hand function, and electrophysiological findings. In addition, continuous SWD seemed to be more effective in reducing symptom severity than pulsed and placebo SWD.